The INPP4B paradox: Like PTEN, but different. (December 2021) - Hamila, Sabryn A.; Ooms, Lisa M.; Rodgers, Samuel J.; Mitchell, Christina A.
Abstract: Cancer is a complex and heterogeneous disease marked by the dysregulation of cancer driver genes historically classified as oncogenes or tumour suppressors according to their ability to promote or inhibit tumour development and growth, respectively. Certain genes display both oncogenic and tumour suppressor functions depending on the biological context, and as such have been termed dual-role cancer driver genes. However, because of their context-dependent behaviour, the tumourigenic mechanism of many dual-role genes is elusive and remains a significant knowledge gap in our effort to understand and treat cancer. Inositol polyphosphate 4-phosphatase type II (INPP4B) is an emerging dual-role cancer driver gene, primarily known for its role as a negative regulator of the phosphoinositide 3-kinase (PI3K)/AKT signalling pathway. In response to growth factor stimulation, class I PI3K generates PtdIns(3, 4, 5)P3 at the plasma membrane. PtdIns(3, 4, 5)P3 can be hydrolysed by inositol polyphosphate 5-phosphatases to generate PtdIns(3, 4)P2, which, together with PtdIns(3, 4, 5)P3, facilitates the activation of AKT to promote cell proliferation, survival, migration, and metabolism. Phosphatase and tensin homology on chromosome 10 (PTEN) and INPP4B are dual-specificity phosphatases that hydrolyse PtdIns(3, 4, 5)P3 and PtdIns(3, 4)P2, respectively, and thus negatively regulate PI3K/AKT signalling. PTEN is a bona fide tumour suppressor that is frequently lost in human tumours. INPP4B was initially characterised as a tumour suppressor akin to PTEN, and has been implicated as such in a number of cancers, including prostate, thyroid, and basal-like breast cancers. However, evidence has since emerged revealing INPP4B as a paradoxical oncogene in several malignancies, with increased INPP4B expression reported in AML, melanoma and colon cancers among others. Although the tumour suppressive function of INPP4B has been mostly ascribed to its ability to negatively regulate PI3K/AKT signalling, its oncogenic function remains less clear, with proposed mechanisms including promotion of PtdIns(3)P-dependent SGK3 signalling, inhibition of PTEN-dependent AKT activation, and enhancing DNA repair mechanisms to confer chemoresistance. Nevertheless, research is ongoing to identify the factors that dictate the tumourigenic output of INPP4B in different human cancers. In this review we discuss the dualistic role that INPP4B plays in the context of cancer development, progression and treatment, drawing comparisons to PTEN to explore how their similarities and, importantly, their differences may account for their diverging roles in tumourigenesis.